Teachers' motivation to work : an exploratory study - Mittal, J. P. (New Delhi, India : Mittal Publications, 1995)
Study focusses on the National Capital Region of Delhi.
Includes bibliographical references
Keywords: Teachers -- Job satisfaction |z India. -- India; Teachers -- Training of -- India